Towards distributed leadership in vocational education and training schools: The interplay between formal leaders and team members. (July 2019) - Bouwmans, Machiel; Runhaar, Piety; Wesselink, Renate; Mulder, Martin
Complex educational innovations in vocational education and training (VET) schools require teamwork and distributed leadership so that team members are enabled to contribute based on their expertise. The literature suggests that distributed leadership is affected by formal leaders' and teachers' actions, but how their actions affect distributed leadership remains largely unknown. Our study, examining what kind of actions affect distributed leadership within VET teacher design teams (TDTs) working on educational innovations, helps to fill this knowledge gap. Individual interviews and group interviews were conducted with three formal leaders (team leaders) and thirteen members of five TDTs from one VET school. These interviews were analysed using thematic analysis. Regarding formal leaders' actions, results showed that team leaders created opportunities for distributed leadership in TDTs, but also set boundaries by, for instance, limiting the scope and making decisions. Regarding teachers' actions, results indicated that TDT members established leader–follower relationships through team learning processes. Furthermore, it was found that distributed leadership in teams changed according to the different phases of the educational innovation. Overall, this study shows that hybrid leadership configurations existed, in which team leaders and teachers played a central role in establishing distributed leadership in teams, and the study indicates that distributed leadership in teams depends on team members' expertise, time and context.